Recent Advancements in Photocatalytic Valorization of Plastic Waste to Chemicals and Fuels - Chen, Aizhu; Yang, Min-Quan; Wang, Sibo; Qian, Qingrong (Frontiers in Nanotechnology, 2021)
The continuous rise in plastic waste raises serious concerns about the ensuing effects on the pollution of global environment and loss of valuable resources. Developing efficient approaches to recycle plastic has been an urgent demand for realizing a sustainable circular economy. Photocatalytic valorization directly utilizes solar energy to transform plastic pollutants into chemicals and fuels, which is hardly implemented by traditional mechanical recycling and incineration strategies, thus offering a promising approach to address the contemporary waste and energy challenges. Here, we focus on the recent advances in the high-value utilization of plastic waste through photocatalysis. The basic principle and different reaction pathways for the photocatalytic valorization of plastic waste are presented. Then, the developed representative photocatalyst systems and converted products are elaborately discussed. At last, the review closes with critical thoughts on research challenges along with some perspectives for further development of this emerging and fascinating field.